The Role of the Traditional Game Congklak as a Medium for Character Education Based on Rahmatan lil ‘Alamin Values of Students in Madrasah Ibtidaiyah Nurul Hidayah - Maulidah, Lida; Nida Fitriyani, Feny; Zubaidi, Zubaidi (AT-TURATS, 2025)
Indonesia is facing a moral crisis that contrasts sharply with the rapid advancement of technology. One way to cultivate character values from an early age is by utilizing congkak as the traditional game. This study explores the role of congklak in shaping rahmatan lil ‘alamin character values among Madrasah Ibtidaiyah students. The research employs a qualitative descriptive approach with field-based study methods to examine the role of the traditional game congklak in character formation aligned with the rahmatan lil ‘alamin student profile at Madrasah Ibtidaiyah Nurul Hidayah, South Tangerang. The data were examined using the Miles, Huberman, and Saldana model combined with source triangulation techniques, resulting in a theoretical insight into the effectiveness of congklak as a tool for character education at Madrasah Ibtidaiyah Nurul Hidayah. The findings highlight that congklak holds a significant role in supporting character education in Madrasah Ibtidaiyah by fostering students' moral, cultural, and social attitudes. In addition to develop cognitive skills such as arithmetic and strategic thinking, this game also helps students cultivate fairness (i‘tidāl), proper manners (ta’addub), and innovative thinking dynamics (tatḥawwur wa ibtikār). The integration of congklak into school learning aligns with the Rahmatan Lil ‘Alamin values of the student profile, which balances intellectual, emotional, and social intelligence to shape a generation with noble character and cultural awareness.Indonesia menghadapi krisis akhlak yang berbanding terbalik dengan pesatnya kemajuan teknologi. Salah satu upaya menanamkan karakter sejak dini adalah dengan permainan tradisional congklak. Penelitian ini mengeksplorasi peran congklak pada pembentukan karakter rahmatan lil alamin pada siswa Madrasah Ibtidaiyah. Penelitian dilakukan dengan arah pendekatan kualitatif secara deskriptif berbasis penelitian lapangan untuk mengetahui peran permainan tradisional congklak dalam pembentukan karakter yang selaras dengan profil peserta didik rahmatan lil alamin di Madrasah Ibtidaiyah Nurul Hidayah Tangerang Selatan. Data dianalisis dengan model Miles, Huberman, Saldana serta teknik triangulasi sumber, sehingga menghasilkan pemahaman teoritis tentang efektivitas permainan congklak sebagai instrumen pendidikan karakter di Madrasah Ibtidaiyah Nurul Hidayah. Hasil penelitian menggarisbawahi bahwa permainan congklak memiliki posisi penting dalam menyokong pendidikan karakter di Madrasah Ibtidaiyah dengan menumbuhkan sikap moral, budaya, dan sosial dari peserta didik. Selain melatih keterampilan kognitif seperti berhitung dan berpikir strategis, permainan ini juga membantu siswa mengembangkan sikap adil (i’tidal), adab yang bagus (ta’addub), juga berpikir dengan dinamika yang inovatif (tathawwur wa ibtikar). Implementasi congklak dalam pembelajaran di madrasah selaras dengan konsep profil pelajar Rahmatan Lil Alamin, yang menyeimbangkan kecerdasan intelektual, emosional, dan sosial untuk membentuk generasi berakhlak mulia dan berwawasan budaya.